Crossing the boundaries gauge dynamics at strong coupling : proceedings of the workshop in honor of the 60th birthday of Misha Shifman, FTPI, University of Minnesota, 14-17 May 2009 (World Scientific Pub. Co., 2010)
This volume contains the proceedings of the workshop "Crossing the Boundaries : Gauge Dynamics at Strong Coupling", hosted by the William I. Fine Theoretical Physics Institute at the University of Minnesota, May 14 - 17, 2009. The workshop honored the 60th birthday of Professor Misha Shifman and his outstanding achievements in the field of gauge dynamics. The meeting attracted a fascinating group of researchers working on the cutting edge of dynamics of gauge theories, including supersymmetric and string theories. Their talks covered a wide area of recent developments in the field